2020
DOI: 10.3390/foods9060808
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Substitution of Rice Flour with Quinoa Flour on the Chemical-Physical, Nutritional, Volatile and Sensory Parameters of Gluten-Free Ladyfinger Biscuits

Abstract: The present study investigates the effect of partial or total substitution of rice flour (RF) with quinoa flour (QF) (at 25%, 50%, 75% and 100%) on the chemical-physical, nutritional, and sensory characteristics, as well as the volatile compounds, of ladyfinger biscuits. All quinoa-based formulations positively affected the crust colour, endowing it with lower ‘lightness’ and higher ‘redness’ values, giving the biscuits a more appealing crust colour. Biscuits with higher percentages of QF also had better struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
42
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(56 citation statements)
references
References 53 publications
13
42
1
Order By: Relevance
“…For the attribute "legume flavour", a clear difference was recorded between control sample and GF biscuits. In example, also, Cannas et al (2020) reported that the employ of an alternative flour, specifically quinoa, gave a more characteristic taste to ladyfinger GF biscuits. It is interesting to observe that "legume flavour" was perceived also in formulations without chickpea or lentil flours due to a more characteristic taste of the flours employed.…”
Section: Liking and Sensory Profiling With Check All That Apply Questionnairementioning
confidence: 99%
See 1 more Smart Citation
“…For the attribute "legume flavour", a clear difference was recorded between control sample and GF biscuits. In example, also, Cannas et al (2020) reported that the employ of an alternative flour, specifically quinoa, gave a more characteristic taste to ladyfinger GF biscuits. It is interesting to observe that "legume flavour" was perceived also in formulations without chickpea or lentil flours due to a more characteristic taste of the flours employed.…”
Section: Liking and Sensory Profiling With Check All That Apply Questionnairementioning
confidence: 99%
“…However, these flours even when employed do not represent the main ingredients in the recipes. It has been reported that the use of more nutrient dense flours could improve the nutritional quality of GF products (Cannas et al, 2020;Di Cairano et al, 2018;Foschia et al, 2016;Martínez-Villaluenga et al, 2020). The use of ingredients rich in rapidly digestible starch and with a low phenolic content can contribute to the increase of blood glucose level (Di Cairano et al, 2020;Moraes et al, 2015;Sun & Miao, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The reason may be attributed to potentially higher water absorbing of QF, since QF recorded higher fiber and fat contents; these results are in agreement with those reported in literature. [2,6] Moreover, QF and WF are considered rich sources of amino acids as shown in Table 2. It is obviously that asparagine (20.33 ± 0.31 g/100 g protein) is the highest amino acid in QF and is 14.7 times higher than that in WF.…”
Section: Chemical Composition and Physical Characterization Of Flours And/or Cakesmentioning
confidence: 99%
“…This observation is in a good agreement with previous studies. [2,31] It was reported that about 20 volatile compounds were detected in high amounts using QF in cookies. The volatile components were mainly aromatics, nitrogen oxides, sulfur compounds, ammonia, and alkanes.…”
Section: Color and Electron Nose Analysesmentioning
confidence: 99%
See 1 more Smart Citation